Hiduik Mamakai and Early Marriage: A Means of Gender Identity for Gambir Peasant Women - Jelly, Jelly; Yulkardi, Yulkardi; Yunarti, Yunarti (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2024)
We want to explain about the lifestyle philosophy of "hiduik mamakai" to the gambir farming community in Minangkabau. The philosophy of hiduik mamakai is the basis for the Minangkabau community of gambir farmers towards the occurrence of early marriage. The philosophy of hiduik mamakai is a view of life regarding the existence of matter used for the pleasure of life. This philosophy also developed as a basis for the Minangkabau community of gambir farmers in carrying out social activities, one of which is marriage. The philosophy of hiduik mamakai has a correlationality to the phenomenon of early marriage in the Minangkabau community of gambir farmers. Some cases of early marriage in gambir farming communities are initiated by the idea that stability can be obtained through marriage even though they are not at the right age or mentality. This is because there is a belief that after marriage there will be a "safe realm" for women to be able to live a lifestyle of "hiduik mamakai". The results of this research indicate that there is a correlational relationship between early marriage and the philosophy of "hiduik mamakai." The philosophy of "hiduik mamakai" is one of the influencing factors, although it is not the sole cause of the phenomenon of early marriage. The causal relationship between these two domains is correlational, not causal. There is no guarantee that the disappearance of the "hiduik mamakai" philosophy will reduce the rate of early marriages. What occurs is that the concept of "hiduik mamakai" philosophy affects the phenomenon of early marriage in a mutually correlating relationship. While it is not the only factor, the philosophy of "hiduik mamakai" is an integral part of the lifestyle of the Minangkabau Gambir farming community. This is because the income of the Gambir farming community is enough to put the economic system on a stable life.